Efavirenz Has the Highest Anti-Proliferative Effect of Non-Nucleoside Reverse Transcriptase Inhibitors against Pancreatic Cancer Cells. - Markus Hecht; Sonja Erber; Thomas Harrer; Hartwig Klinker; Thomas Roth; Hans Parsch; Nora Fiebig; Rainer Fietkau; Luitpold V Distel (PLoS ONE, 2015)
Cancer prevention and therapy in HIV-1-infected patients will play an important role in future. The non-nucleoside reverse transcriptase inhibitors (NNRTI) Efavirenz and Nevirapine are cytotoxic against cancer cells in vitro. As other NNRTIs have not been studied so far, all clinically used NNRTIs were tested and the in vitro toxic concentrations were compared to drug levels in patients to predict possible anti-cancer effects in vivo.Cytotoxicity was studied by Annexin-V-APC/7AAD staining and flow cytometry in the pancreatic cancer cell lines BxPC-3 and Panc-1 and confirmed by colony formation assays. The 50% effective cytotoxic concentrations (EC50) were calculated and compared to the blood levels in our patients and published data.The in vitro EC50 of the different drugs in the BxPC-3 pancreatic cancer cells were: Efavirenz 31.5 μmol/l (= 9944 ng/ml), Nevirapine 239 μmol/l (= 63,786 ng/ml), Etravirine 89.0 μmol/l (= 38,740 ng/ml), Lersivirine 543 μmol/l (= 168,523 ng/ml), Delavirdine 171 μmol/l (= 78,072 ng/ml), Rilpivirine 24.4 μmol/l (= 8941 ng/ml). As Efavirenz and Rilpivirine had the highest cytotoxic potential and Nevirapine is frequently used in HIV-1 positive patients, the results of these three drugs were further studied in Panc-1 pancreatic cancer cells and confirmed with colony formation assays. 205 patient blood levels of Efavirenz, 127 of Rilpivirine and 31 of Nevirapine were analyzed. The mean blood level of Efavirenz was 3587 ng/ml (range 162-15,363 ng/ml), of Rilpivirine 144 ng/ml (range 0-572 ng/ml) and of Nevirapine 4955 ng/ml (range 1856-8697 ng/ml). Blood levels from our patients and from published data had comparable Efavirenz levels to the in vitro toxic EC50 in about 1 to 5% of all patients.All studied NNRTIs were toxic against cancer cells. A low percentage of patients taking Efavirenz reached in vitro cytotoxic blood levels. It can be speculated that in HIV-1 positive patients having high Efavirenz blood levels pancreatic cancer incidence might be reduced. Efavirenz might be a new option in the treatment of cancer.